Use of a bioengineered antioxidant in mouse models of metabolic syndrome. (1st February 2020) - Griffin, Deric M.; Bitner, Brittany R.; Criss Ii, Zachary; Marcano, Daniela; Berlin, Jacob M.; Kent, Thomas A.; Tour, James M.; Samson, Susan L.; Pautler, Robia G.
ABSTRACT: Background : Oxidative stress has been implicated in metabolic syndrome (MetS); however, antioxidants such as vitamin E have had limited success in the clinic. This prompts the question of what effects amore potent antioxidant might produce. A prime candidate is the recently developed bioengineered antioxidant, poly(ethylene glycol)-functionalizedhydrophilic carbon clusters (PEG-HCCs), which are capable of neutralizing the reactive oxygen species (ROS) superoxide anion and hydroxyl radical at10 6 /molecule of PEG-HCC. In this project, we tested the potential of PEG-HCCs as a possible therapeutic for MetS. Results : PEG-HCC treatment lessened lipid peroxidation, aspartate aminotransferase levels, non-fastingblood glucose levels, and JNK phosphorylation inob/ob mice. PEG-HCC-treated WT mice had an increased response to insulin by insulin tolerance tests and adecrease in blood glucose by glucose tolerance tests. These effects were not observed in HFD-fed mice, regardless of treatment. PEG-HCCs were observed in the interstitial space of liver, spleen, skeletal muscle, and adipose tissue. No significant difference was shown in gluconeogenesis or inflammatory gene expression between treatment and dietary groups. Expert Opinion : PEG-HCCs improved some parameters of disease possibly due to a resulting increase in peripheral insulin sensitivity. However, additional studies are needed to elucidate how PEG-HCCsare producing these effects.